The Relationship Of Services And Promotion With Purchase Decisions At Dewi Cell Counter, Kaur District - Restu Sukri; Karona Cahya Susena; Eska Prima M. D. (Penerbit Jurnal Indonesia, 2021)
This study aims to determine the correlation between service and purchasing decisions at Counter Dewi Cell of Kaur Regency and to determine the correlation between promotion and purchasing decisions at Counter Dewi Cell of Kaur Regency. The analytical method used is the Spearman rank correlation and hypothesis testing. Respondents of this study were 75 buyers. From the calculation of the spearman rank correlation coefficient for the correlation between service and purchasing decisions at Counter Dewi Cell of Kaur Regency, the calculated rho value is 0.863 which means it is very strong, because the correlation value lies in the correlation coefficient interval from 0.800 to 1,000, and from the hypothesis test with the t test shows that tcount > ttable (14,572> 1,666) then Ho is rejected and Ha is accepted means that service has a significant correlation with purchasing decisions at Counter Dewi Cell of Kaur Regency. While the calculation of the spearman rank correlation coefficient for the correlation between promotion and purchasing decisions at Counter Dewi Cell of Kaur Regency obtained a calculated rho value of 0.777 which means strong, because the correlation value lies in the correlation coefficient interval from 0.600 to 0.799, and from the hypothesis test with the t test shows that tcount > ttable (10.535> 1.666) then Ho is rejected and Ha is accepted means that promotion has a significant correlation with purchasing decisions at Counter Dewi Cell of Kaur Regency.